Adolescents who stay, parents who migrate: gender inequalities, resilience and coping strategies in Tajikistan - Nazridod, S. (2021)
Studies on the consequences of migration often ignore the perspectives of children and adolescents who remain in the origin country while their migrant parents are absent. This is the case in Tajikistan, one of the poorest and most remittance-dependent countries in the world. Using a qualitative methodology, microethnography, we interviewed eight teenagers aged between 12 and 18, in the city of Khorugh, Tajikistan, to explore the impact of migration from their perspective. Findings reveal that these adolescents ‘understand’ the reasons for their parents’ migration in a way that both gives coherence to this migration and invests young people with resilience and coping strategies. As a result, all the young people naturalised having to live with sadness, reflecting the ‘normalisation’ of this social cost in wider Tajik society. However, the experiences and coping strategies of those interviewed are gendered; boys were more likely to ‘rationalise’ their experience and be aloof; girls more likely to express emotional upset. In practical terms, boys also received more benefits from remittances while girls reported feeling overwhelmed by domestic chores expected of them. Through this study, we contribute to the recent literature on the lived experiences and agency of non-migrant teenagers.